2020
DOI: 10.31234/osf.io/84d2c
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differences between health workers and general population in risk perception, behaviors, and psychological distress related to COVID-19 spread in Italy.

Abstract: In this study, we investigated the perception of risk and the worries about COVID-19 infection in both healthcare workers and general population in Italy. We studied the difference in risk perception in these two groups, and how this related to demographic variables and psychological factors such as stress, anxiety, and death anxiety. To this aim, we administered an online questionnaire about COVID-19 together with other questionnaires assessing the psychological condition of participants. First, we found that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 35 publications
5
49
2
5
Order By: Relevance
“…The data on parents' internalizing symptoms suggest that fear of contagion is an important psychological factor that negatively impacts psychological well-being of healthy adult individuals, subject to isolation and confinement to prevent spread of the new coronavirus. This is in line with results of previous studies showing that fear of infection was a significant stressor during quarantine (see the reviews by Brooks et al, 2020) or, more generally but specifically related to Covid-19, that higher perceived risk of infection increased individuals' stress and anxiety (Simione and Gnagnarella, 2020). Of interest, in one study investigating the school's communities response to school closure during the H1N1 2009 influenza pandemic (Braunack-Mayer et al, 2013), it was found that the individuals who were more concerned about becoming infected or spreading the virus to others tended to be those with young children (or to be pregnant women).…”
Section: Discussionsupporting
confidence: 91%
“…The data on parents' internalizing symptoms suggest that fear of contagion is an important psychological factor that negatively impacts psychological well-being of healthy adult individuals, subject to isolation and confinement to prevent spread of the new coronavirus. This is in line with results of previous studies showing that fear of infection was a significant stressor during quarantine (see the reviews by Brooks et al, 2020) or, more generally but specifically related to Covid-19, that higher perceived risk of infection increased individuals' stress and anxiety (Simione and Gnagnarella, 2020). Of interest, in one study investigating the school's communities response to school closure during the H1N1 2009 influenza pandemic (Braunack-Mayer et al, 2013), it was found that the individuals who were more concerned about becoming infected or spreading the virus to others tended to be those with young children (or to be pregnant women).…”
Section: Discussionsupporting
confidence: 91%
“…HCWs in these areas expressed higher mental disturbance than those in other regions [4,20]. Also, medical staff working in North Italy with the highest number of patients reported higher levels of anxiety and stress than HCWs or the general public from other regions of Italy [22].…”
Section: Resultsmentioning
confidence: 87%
“…Andrew Wooyoung Kim et al (Pfefferbaum & North, 2020;Zhang & Ma, 2020). Studies from China, Italy, and the USA show that perceived severity of the pandemic, psychological distress from COVID-19, and increased risk perceptions predicted poorer psychiatric outcomes (Ding et al, 2020;Li, Yang, Dou, & Cheung, 2020;Rodriguez, Litt, & Stewart, 2020;Simione & Gnagnarella, 2020). The opposite may also be truelearned hopelessness and increased stress sensitivity characteristic of depression may lead to worse appraisals of stressful conditions, such as heightened perceptions of disease risk (Folkman & Lazarus, 1986;Luseno et al, 2020;Rovner, Haller, Casten, Murchison, & Hark, 2014).…”
Section: Discussionmentioning
confidence: 99%